Financial statements disclosure on Indonesian local government websites - Wahyudin Nor; Muhammad Hudaya; Rifqi Novriyandana (Asian Journal of Accounting Research, 2019)
The purpose of this paper is to examine the extent to which audit opinion, audit findings, follow-up audit recommendations, level of education, level of welfare and heads of local governments’ commitment influence the disclosure of financial statements on the official website of local government.The data of this research comprise 68 financial statements during the period 2015–2016 collected from 34 local governments across Indonesia by employing the census method. The data then are analyzed using logistic regression.The results of this study show that audit opinion has a positive significant influence on the disclosure of financial statements on local government websites in Indonesia, while the audit findings, follow-up audit recommendations, level of education, level of welfare and heads of local governments’ commitment have no significant influences on the disclosure of financial statements local governments’ websites across Indonesia.The study contributes to the public sector accounting research by enhancing our understanding to the disclosure of financial statements on local government websites.